2012
DOI: 10.1073/pnas.1200072109
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D accelerates resolution of inflammatory responses during tuberculosis treatment

Abstract: Calcidiol, the major circulating metabolite of vitamin D, supports induction of pleiotropic antimicrobial responses in vitro. Vitamin D supplementation elevates circulating calcidiol concentrations, and thus has a potential role in the prevention and treatment of infection. The immunomodulatory effects of administering vitamin D to humans with an infectious disease have not previously been reported. To characterize these effects, we conducted a detailed longitudinal study of circulating and antigen-stimulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
204
4
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 279 publications
(230 citation statements)
references
References 44 publications
5
204
4
8
Order By: Relevance
“…Vitamin D supplementation can also attenuate inflammation and accelerate sputum smear conversion in patients with tuberculosis. 42 These findings on vitamin D and infectious diseases support the immunomodulating role of vitamin D in the pathophysiology of sepsis. 11,12,41,42 The United States Endocrine Society 21 recommends identification of vitamin D deficiency and treatment of the deficiency with vitamin D supplementation.…”
Section: Multivariate Analysismentioning
confidence: 76%
See 1 more Smart Citation
“…Vitamin D supplementation can also attenuate inflammation and accelerate sputum smear conversion in patients with tuberculosis. 42 These findings on vitamin D and infectious diseases support the immunomodulating role of vitamin D in the pathophysiology of sepsis. 11,12,41,42 The United States Endocrine Society 21 recommends identification of vitamin D deficiency and treatment of the deficiency with vitamin D supplementation.…”
Section: Multivariate Analysismentioning
confidence: 76%
“…42 These findings on vitamin D and infectious diseases support the immunomodulating role of vitamin D in the pathophysiology of sepsis. 11,12,41,42 The United States Endocrine Society 21 recommends identification of vitamin D deficiency and treatment of the deficiency with vitamin D supplementation. In our study, patients who had supplementation with ergocalciferol or cholecaciferol before admission had significantly lower hospital and 90-day mortality than did patients who were not receiving supplementation.…”
Section: Multivariate Analysismentioning
confidence: 76%
“…2. People who do not supplement may expect to have greater susceptibility to infectious diseases such as tuberculosis (39) and viruses (40)(41)(42) , which have been shown to respond to vitamin D supplementation in clinical trials through improved innate immunity, with increased production of cathelicidin and other natural bacteriocides. 3.…”
Section: Harms Consequent Upon False Inference Of Reverse Causationmentioning
confidence: 99%
“…Coussens et al reported an analysis of markers of immune and inflammatory response in a subset of participants from a randomized clinical trial of vitamin D 3 supplementation in culturepositive pulmonary tuberculosis (1). In that trial, the vitamin D intervention did not alter the primary endpoint, time to sputum culture conversion (2), a result that is congruent with that from another randomized controlled trial, in which a clinical severity score was not improved by vitamin D supplementation (3).…”
mentioning
confidence: 84%